PEDAGOGICAL REFLECTION AS A METHOD OF PROFESSIONALLY-ORIENTED FORMATION OF SOCIO-CULTURAL COMPETENCE AT FUTURE FOREIGN LANGUAGE TEACHER TRAINING - Smirnova, Elena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The language policy focus on multilingualism and multicultural education necessitated to train a foreign language teacher who is able to teach students efficient cooperation in multilingual and multicultural environment. Young teachers face into difficulties when passing from the social role of a student to the social role of a teacher, so far as language training at university is to a greater extent subject-related rather than professionally-oriented. The main goal of the paper is to view vocational training peculiarities of future foreign language teachers from the perspective of socio-cultural approach. The article presents professionally-oriented ways of socio-cultural competence formation of a future teacher at a practical foreign language lesson. The author proves that the decisive condition to ensure the professional direction of socio-cultural competence formation is pedagogical reflection, which makes it possible to get students involved in the reflective development of the inner space of their future professional activity. The proposed system of tasks is aimed to involve students in the reflective analysis of their own strategies how to learn a foreign culture, their functional role in the process of education and, on the other hand, to make sense of the teacher’s performance and the professional relevance of the educational process. As the way of evidence of the proposed tasks efficiency, the observation   results on students at teaching practice and school teachers’ survey data are given.